Current perspectives for metabolomics and lipidomics in dyslipidemia of acne vulgaris: a mini review - Wu, Liang; Zhu, Sheng-Cai; He, Yang; Zhu, Yun-Xia; Ou-Yang, Xiao-Liang; Zhang, Deng; Li, Chun-Ming (Frontiers in Medicine, 2025)
Acne vulgaris (AV) is a common inflammatory disorder involving the pilosebaceous unit. Many studies have reported that people with AV have higher levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-c) compared to healthy controls. Hence, they concluded that an unhealthy lipid profile is an independent risk factor for AV. Recent research in metabolomics and lipidomics has been propelled by rapid advancements in technologies including computational methods and mass spectrometry. Using metabolomics and lipidomics approach, a broad range of structurally diverse lipid species were detected and important lipid biomarkers were identified that are vital to the pathogenesis of AV. In this review, we will describe the recent progress in dyslipidemia of AV using metabolomics and lipidomics advances. We will begin with a literature overview of dyslipidemia of AV, followed by a short introduction of metabolomics and lipidomics. Finally, we will focus on applying metabolomics and lipidomics in dyslipidemia of AV.